"Passing the Baton": The effects of CEO succession planning on firm performance and volatility. (17th September 2018) - Tao, Ran; Zhao, Hong
Abstract: Manuscript Type: Empirical Research Question/Issue: This paper seeks to understand the way in which CEO succession planning affects firm performance and volatility during CEO turnover. Specifically, the paper examines a succession type referred to as relay succession, in which the incoming CEO has been groomed as an heir apparent before the turnover. Research Findings/Insights: Heirs apparent are identified by comparing all of a firm's non‐CEO top executives' promotion likelihood estimated based on a set of characteristics. Applying this heir apparent measure to a large sample of CEO turnovers from ExecuComp, the paper delivers robust evidence that firms with relay successions achieve higher post‐turnover accounting performance, higher long‐term stock returns, and lower volatility. Further, the positive effect of relay succession on performance is stronger for firms with higher human capital requirements. Theoretical/Academic Implications: The paper provides comprehensive evidence of the important role of relay succession in smoothing CEO transitions. It also sheds new light on previous research on outside successions by showing that the difference between inside and outside successions is explained largely by the length of relay. Practitioner/Policy Implications: The paper suggests that firms should consider using relay succession to improve performance and reduce volatility during the CEO transition period. The paper's findings also support the US Securities and Exchange Commission's recent appeal for more firm disclosure on its succession planning.